2002
DOI: 10.1109/22.989955
|View full text |Cite
|
Sign up to set email alerts
|

Digital microwave receiver technology

Abstract: This paper reports the impact of digital signal processing on microwave receiver technology. The majority of modern receiver designs are based on digital technology. Wideand narrow-band receivers will be presented. The wide-band receivers cover approximately 1-GHz instantaneous bandwidth and are used to intercept radar pulses. Current narrow-band receivers cover up to 50-MHz instantaneous bandwidth and are primarily used for receiving communication signals. Two approaches for wide-band receiver design will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Though some commercial systems such as those of Geophysical Survey Systems Inc. (GSSI) and Sensors and Software have the advantage of accuracy and sampling rate, they use an analog sampling gate to convert signals to audio range. This process may lose some information (Tsui and Stephens, 2002). Compared with these commercial systems, our system has no analog sampling gate or analog-to-digital conversion, and integrates the analog-to-digital circuit and the control circuit together to form a cohesive whole.…”
Section: Sampling Controllermentioning
confidence: 99%
“…Though some commercial systems such as those of Geophysical Survey Systems Inc. (GSSI) and Sensors and Software have the advantage of accuracy and sampling rate, they use an analog sampling gate to convert signals to audio range. This process may lose some information (Tsui and Stephens, 2002). Compared with these commercial systems, our system has no analog sampling gate or analog-to-digital conversion, and integrates the analog-to-digital circuit and the control circuit together to form a cohesive whole.…”
Section: Sampling Controllermentioning
confidence: 99%
“…The input RF signal is down converted into intermediate frequency (IF) and digitized using a high-speed analog to digital converter (ADC). This process retains all information and the digital receiver produces an overall better performance than the analog counterpart [1].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, there appear big discrepancies between the calculated P f a and the theoretical one deduced for continous gaussian noise samples. 5 It can be observed that the calculated curve has steps due to the fact that both the real and the imaginary parts of the output are integers, so that the module range is not continuous. …”
Section: Impact Of the Butterfly Truncationmentioning
confidence: 99%
“…Figure 19 shows the difference between the theoretical and the calculated P f a curves when σ = 256. 5 For lower values of σ, the butterfly truncation modifies the probability density functions of the noise samples. As a consequence, there appear big discrepancies between the calculated P f a and the theoretical one deduced for continous gaussian noise samples.…”
Section: Impact Of the Butterfly Truncationmentioning
confidence: 99%
See 1 more Smart Citation